2008
DOI: 10.1021/bm800683f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Study of the Curcumin−Casein Micelle Complexation and Its Application as a Drug Nanocarrier to Cancer Cells

Abstract: In milk caseins exists a natural nanostructure, which can be exploited as a carrier of hydrophobic drugs. Here we investigated the complex formation of curcumin with bovine casein micelles (CMs) and its use as a vehicle for drug delivery to cancer cells. DLS studies of the CM suspension that was stable in buffer solution (pH 7.4) showed an average size distribution of <200 nm. SEM and AFM studies showed that the particles were roughly spherical in shape. Steady-state fluorescence spectroscopy of the CM-curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
260
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(290 citation statements)
references
References 48 publications
19
260
2
Order By: Relevance
“…In the literature, cytotoxicity studies of HeLa cells showed that the IC 50 of free curcumin and complexed curcumin on bovine casein micelles was 14.85 and 12.69 μM, respecttively. The loaded curcumin has showed a cytotoxic effect that was comparable to that of free curcumin [17]. In this study, as control, Hela cells were kept in the culture medium without any treatment.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, cytotoxicity studies of HeLa cells showed that the IC 50 of free curcumin and complexed curcumin on bovine casein micelles was 14.85 and 12.69 μM, respecttively. The loaded curcumin has showed a cytotoxic effect that was comparable to that of free curcumin [17]. In this study, as control, Hela cells were kept in the culture medium without any treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The main advantages of such materials are the high biocompatibility and improved CUR efficiency on cervical (Sahu et al, 2008b;Curcio et al, 2015a) and lung (Curcio et al, 2015b) cancer cells in vitro and ovarian cancer with negligible immunogenicity in mice (Podaralla et al, 2012). Amphiphilic behavior was conferred to CT by conjugation with STA, allowing the obtainment of CUR carrier for the treatment of colon cancer both in vitro (primary cancer cells) and in vivo (orthotopic mice) with improved efficiency (Wang et al, 2012b).…”
Section: Polymeric Vesicular Systemsmentioning
confidence: 99%
“…This depicts similar surroundings for Cur in both Cur NLCs and Cur-TCA 50 NLCs, which could be described by Cur encapsulation in the apolar core. 37 However, dashed arrows in Figure 2D specify the spectral shoulder of the native Cur at 350 nm, thus implying Cur presence in the polar environment, as supported by Leung and Kee. 1 h-NMr spectrum of s100 and s100-Tca (B); cur-Tca Nlcs for oral delivery of cur using bile-acid transporter (C).…”
Section: Preparation and Characterization Of Cur-tca Nlcsmentioning
confidence: 60%